Synthesis of magnetic iron oxide nanoparticles toward arsenic removal from drinking water - Starbird-Pérez, Ricardo (2015)
The aim of this study is to provide a material with large contact area, to be used in the removal of arsenic from water sources. This work report on the synthesis of iron nanoparticles with superparamagnetic properties, stabilized using stearic acid and their respective characterization by infrared spectrophotometric, thermogravimetric and electronic transmission techniques. The presence of an emulsifier is decisive for the stabilization of iron oxide phase (maghemite or magnetite) with magnetic properties. The resulting material shows promissory properties to be used for drinking water treatment.